Amino acid production exceeds plant nitrogen demand in Siberian tundra - Birgit Wild (Department of Microbiology and Ecosystem Science, Centre for Microbiology and Environmental Systems Science, University of Vienna); Ricardo J Eloy Alves (Department of Ecogenomics and Systems Biology, Faculty of Life Sciences, University of Vienna); Jiři Bárta (Department of Ecosystem Biology, University of South Bohemia); Petr Čapek (Department of Ecosystem Biology, University of South Bohemia); Norman Gentsch (Institute of Soil Science, Leibniz Universität Hannover); Georg Guggenberger (Institute of Soil Science, Leibniz Universität Hannover); Gustaf Hugelius (Bolin Centre for Climate Research, Stockholm University); Anna Knoltsch (Department of Microbiology and Ecosystem Science, Centre for Microbiology and Environmental Systems Science, University of Vienna); Peter Kuhry (Department of Physical Geography, Stockholm University); Nikolay Lashchinskiy (Central Siberian Botanical Garden, Siberian Branch of Russian Academy of Sciences); Robert Mikutta (Soil Science and Soil Protection, Martin Luther University Halle-Wittenberg); Juri Palmtag (Department of Physical Geography, Stockholm University); et al. (Environmental Research Letters, 2018)
The abstract is available here: https://uscholar.univie.ac.at/o:1032854 The abstract is available here: https://uscholar.univie.ac.at/o:1032854